Awareness of and responsiveness to environmental issues: Views from secondary school students in Trinidad and Tobago - Maharaj-Sharma, Rawatee (My University, 2016)
In a study in Trinidad and Tobago involving 176 secondary school students aged 15-17 years, it was found that percent of the group had a good working knowledge about environmental issues. More students from rural schools were found to be personally aware of specific environmental issues in their communities, while more urban students indicated that they had done something tangible about one or more environmental issues. The students were surveyed by way of a 2-sectioned attitudinal-based opinionnaire, which gauged general knowledge and awareness in the first section and students' responsiveness in the second section. The results showed the while both urban and rural students were highly aware of environmental issues, rural students were slightly more responsive to these issues. A small percentage of students in this work were found to have a weak knowledge base about environmental issues, were generally indifferent to environmental issues within their communities, and had never been involved in any initiative on environmental matters
Keywords: Secondary school students; Environmental awareness; Student attitudes; Knowledge level; Urban areas; Rural areas; Trinidad and Tobago